Quantitative Analysis of Retinal Ganglion Cell Survival with Rbpms Immunolabeling in Animal Models of Optic Neuropathies - Kwong, Jacky M. K. (Association for Research in Vision and Ophthalmology, Inc., 2011)
PURPOSE. To investigate whether a recently described retinal ganglion cell (RGC) marker Rbpms (RNA binding protein with multiple splicing) could be used for RGC quantification in various models of RGC degeneration. METHODS. Optic nerve crush, excitotoxicity, and elevated intraocular pressure (IOP) rat models were used. Topographic analysis of Rbpms immunolabeling was performed on retinal wholemounts. Retrograde labelings with Fluorogold (FG) and III β-tubulin immunohistochemistry were compared. RESULTS. In the optic nerve crush model, 37%, 87%, and 93% of Rbpms-positive cells were lost 1, 2, and 4 weeks, respectively. Significant loss of Rbpms-positive cells was noted 1 week after intravitreal injection of 12, 30, and 120 nmol N-methyl-d-aspartate (NMDA), whereas coinjection of 120 nmol of NMDA along with MK-801 increased the cell number from 10% to 59%. Over 95% of Rbpms-positive cells were FG- and III β-tubulin–positive after injury caused by optic nerve crush and NMDA injection. In rats with elevated IOP, induced by trabecular laser photocoagulation, there was a significant loss of Rbpms-positive cells compared with that of contralateral controls (P = 0.0004), and cumulative IOP elevation showed a strong linear relationship with the quantification of RGCs by Rbpms immunolabeling and retrograde labeling with FG. More than 99% of the remaining Rbpms-positive cells were double-labeled with FG. CONCLUSIONS. Rbpms can reliably be used as an RGC marker for quantitative evaluation in rat models of RGC degeneration, regardless of the nature and the location of the primary site of the injury and the extent of neurodegeneration.